IMPLEMENTASI PERATURAN WALIKOTA PEKANBARU - Riski Yanto, Zaili Rusli, Febri Yuliani (JIANA ( Jurnal Ilmu Administrasi Negara ), 2019)
Implementation of Pekanbaru Mayor Regulation. This study aims to find out andanalyze the implementation and factors that influence the Implementation of the Regulation of theMayor of Pekanbaru. This type of research is a qualitative research method approach. Primary datacollection through interviews with research informants is the Assistant Head of Organization andSecretary of the City Government. The results of the study show that it is necessary to amend theRegulation of the Mayor